The effect of spraying a dry bread yeast suspension and a licorice root extract on cauliflower plant growth and yield (Brassica oleracea var. botrytis) - Zainab A. Al-sudani; Zainab A. Al-sudani; Omar A. Ibrahim; Faris I. Obaid; Abdulla A. Abdulla (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ)
The present work is an endeavor to examine the impact of spraying via a suspension of yeast origin and an extract of licorice roots. We focused on three distinct concentrations of (20.10.0) g L-1 to investigate their effects on the growth and yield of cauliflower plants. The experiment was conducted in an agricultural station affiliated with the College of Agriculture, University of Basrah, in the Garmat Ali region during the winter agrarian season 2022-2023. The study's findings showed that a spray concentration of 10 g L-1 of the dry yeast suspension significantly increased plant height, leaf area, dry weight of the plant, curd diameter, weight, and yield, In contrast a concentration of 20 g L-1 significantly increased the total soluble solid (TSS) in the curd. Moreover, the plants sprayed with licorice root extract at a concentration of 10 g L-1 showed significant increases in plant height, the number of leaves, leaf area, dry weight, curd diameter and weight, total yield, and the percentage of total soluble solids in the curd. Additionally, the concentration of 20 g L-1 significantly increased the chlorophyll and carotene pigments in the leaves.